Effect of pressure cycles and thermal conditions on the reliability of a high-pressure diecast Al alloy heating radiator. (November 2019) - Timelli, Giulio; De Mori, Alessandro; Haghayeghi, Reza
Abstract: The fatigue reliability of a diecast AlSi11Cu2(Fe) alloy radiator has been investigated at different pressure amplitudes and thermal exposure. Based on failure mode analysis, two failure mechanisms are observed during fatigue testing, i.e. leakage at the interface between the diecast element and the plug, and fatigue fracture of a radiator element. Fatigue life tests have been carried out at two different pressure amplitudes, 3 and 4 MPa, and two holding temperatures, 40 and 60 °C, respectively. The results reveal how the main cause of failure is related to the fatigue failure of a radiator element in the whole heating system. This is due to casting defects such as gas porosity and oxides which are formed during the filling phase of the die cavity in high-pressure die casting. Furthermore, casting defects increase the leakage failure and reduce the fatigue life of the radiator. An increase of the holding temperature increases the frequency of leakage failure of radiators.